The influence of E-Commerce on the function of space and the environment in the Home Industry area (Case Study: Home industry in Rw.03 , Kel. Cibaduyut , Bandung City) - Yulistian, Saldi; Metra, Pol (Sustainability (STPP) Theory, Practice and Policy, 2022)
Digital information technology is developing quite rapidly in Indonesia, opening up new opportunities as well as challenges in various fields of daily life, because in the era of development of digital information technology it touches various aspects of life. One aspect is the cottage industry sector. The use of digital information technology in the home industry can facilitate buying and selling activities and promotions in E-Commerce stalls without having to meet face-to-face between sellers and buyers. For most business actors, production, distribution, sales, and promotion activities are carried out in the same place, namely at home/production workshop. Activities carried out in the same place cause changes in the space and environment for both the business actors themselves and the surrounding environment. In addition, these activities will also affect socio-economic changes and environmental changes, considering that the location of this research is in a dense village with almost no distance between houses. The research is located in Rw. 03 Cibaduyut sub-district, Bandung City with the majority of respondents having businesses made from leather such as; shoes and sandals. This study uses an approach through direct observation, interviews and surveys. The results of the study reveal the effect of E-Commerce on space and the environment in the cottage industry area. So that this research can be used to see the behavior of the community and the needs of industry players in structuring a dense village environment.